The Baktrian Coregency Legend Coinage of Seleukos and Antiochos: Context and Origin - Taylor, Lloyd W. H. (KOINON: The International Journal of Classical Numismatic Studies, 2023)
The light weight standard coregency legend coinage of Seleukos and Antiochos struck at the mint of Ai Khanoum in Baktria is an enigmatic punctuation of the otherwise consistently Attic weight standard coinage of the Seleukid realm in the 3rd century BC. A newly identified coregency legend gold stater weighing c.7.05 grams establishes that the coregency coinage system was a comprehensive trimetallic coinage. Consistent with this reduced weight standard stater is the tetradrachm weight standard of c. 14.10 grams. This coinage briefly displaced the previously issued Attic weight coinage in the Oxus valley. A reappraisal of the coinage and its context leads to the conclusion that the impetus for its mintage was the creation of a closed monetary system in the Oxus valley, seeking to emulate the success of Ptolemy in the Nile valley. This extended a pattern of Seleukid adoption and adaptation of Ptolemaic innovations. A motivating factor in this regard was the absence of an indigenous source of silver in the Oxus valley at a time when an influx of Greek settlers catalysed a rapid growth in the monetary economy. However, changing demographics, permeable frontiers, and the assassination of Seleukos contributed to the abandonment of this epichoric coinage, marking the collapse of a dedicated Seleukid effort to rapidly advance the development of monetized economies in eastern reaches of the kingdom.